2022
DOI: 10.1093/g3journal/jkac021
|View full text |Cite
|
Sign up to set email alerts
|

A large deletion at the cortex locus eliminates butterfly wing patterning

Abstract: As the genetic basis of natural and domesticated variation has been described in recent years, a number of hotspot genes have been repeatedly identified as the targets of selection, Heliconius butterflies display a spectacular diversity of pattern variants in the wild and the genetic basis of these patterns has been well-described. Here we sought to identify the mechanism behind an unusual pattern variant that is instead found in captivity, the ivory mutant, in which all scales on both the wings and body becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 98 publications
2
13
0
Order By: Relevance
“…3C). This phenotype resembled the original H. melpomene ivory spontaneous mutants (13), where almost all melanins appeared to be lost, and only weak traces of presumptive ommochrome pigmentation remained. ivory Δ17kb did not prove to be embryonic lethal, although homozygous butterflies were flightless and not as active as heterozygotes or wildtypes.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…3C). This phenotype resembled the original H. melpomene ivory spontaneous mutants (13), where almost all melanins appeared to be lost, and only weak traces of presumptive ommochrome pigmentation remained. ivory Δ17kb did not prove to be embryonic lethal, although homozygous butterflies were flightless and not as active as heterozygotes or wildtypes.…”
Section: Resultssupporting
confidence: 67%
“…These data identified a lncRNA that partially overlaps with the 5' end of the cortex gene. The 3' region of this predicted lncRNA also overlaps with the previously described 78kb ivory mutation -a spontaneous deletion identified in Heliconius melpomene that produced largely unpigmented butterflies (13) -thus, this novel lncRNA is dubbed ivory after the original Heliconius mutation.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…When the effector gene is a poorly annotated non-coding element that acts in trans , such as mir-193 or its primary transcript ivory investigated in this study, a direct link between local genetic variation and flanking protein-coding genes can lead to misleading conclusions. This happened with the cortex locus where a large number of intraspecific wing color pattern polymorphisms in lepidopterans, in most cases involving black and white, or dark and bright color patterns, have been mapped to this hotspot locus and been mistakenly attributed to cortex regulation ( 2, 5, 7, 15, 17 ). It will be interesting to examine in future how the genomic contexts and targets of mir-193 have evolved across animals and how, ebony , one of the targets of mir-193 in B. anynana , became the hotspot locus across Drosophila species ( 37 ), despite the presence and conserved function of mir-193 .…”
Section: Mir-193 Is An Ancestral Melanic Color Regulatormentioning
confidence: 99%
“…Functional studies using CRISPR-Cas9 suggested that cortex might promote wing melanization. These studies, however, suffered from low success rates ( 2, 15, 17 ), hinting that hidden genomic features next to cortex , rather than cortex itself, could be causative. While previous investigations exclusively focused on protein-coding genes, non-coding RNAs were ignored, despite the presence of two micro-RNAs (miRNAs) at this locus ( 18 ).…”
mentioning
confidence: 99%